Effect of TiO2 – SiO2 hybrid nanofluids on enhanced oil recovery process under different wettability conditions - Afshin Goharzadeh; Yap Yit Fatt; Jitendra S. Sangwai (Capillarity, 2023)
The effect of TiO2–SiO2 hybrid nanofluid on the enhanced oil recovery process is experimentally investigated. The flooding efficiency is measured for a flooding process in an initially oil-filled transparent micro-porous medium. Measurements were performed for two different surface wettability conditions, namely water-wet and neutral-wet. The average nanoparticle size, viscosity, surface tension, and contact angle of TiO2–SiO2 hybrid nanofluid are reported. The flooding efficiency of the hybrid nanofluid is compared with that of SiO2 nanofluid and TiO2 nanofluid. The experimental results reveal that for neutral-wet surface condition, SiO2 nanofluid achieves the best recovery, whereas for water-wet surface condition, TiO2–SiO2 hybrid nanofluid produces the best flooding efficiency. Obtained results showed that TiO2 nanofluid is unstable, with larger aggregated particles settling under gravity, and therefore not suitable for the flooding process by itself. The efficiency of hybrid nanofluid flooding depends significantly on fluid stability, wettability of the porous wall, surface tension, and contact angle of the three phases (crude oil, nanofluid solution, and solid surface). The TiO2–SiO2 hybrid nanofluid reduces surface tension while increasing contact angle and solution stability. Document Type: Original article Cited as: Goharzadeh, A., Fatt, Y. Y., Sangwai, J. S. Effect of TiO2 – SiO2 hybrid nanofluids on enhanced oil recovery process under different wettability conditions. Capillarity, 2023, 8(1): 1-10. https://doi.org/10.46690/capi.2023.07.01